Analysis of Vintage Area and Divestment Strategy as a Determination Level Strategy - Yustini, Tien; Sanusi, Anuar (Opción, 2019)
The slowdown in the growth of the financing industry in Indonesia in the past two years is a result of the general economic slowdown. Although it continues to grow amid an economic slowdown, the problem facing the financing industry is the capital problem, besides the level of competition with the banking sector which is aggressively lending, it is also a problem that is always faced by the financing business in Indonesia. This study bertujuan to analyze the factors Vintage Area and divestments Strategy as one determinant of open- ing or closing of perus Ahaan branches in several cities . The primary data in this study are in the form of explanations and opinions by several parties in the company related to the company’s condition, the process of opening and closing branches at PQR Finance Enterprise. Secondary data obtained by researchers from various sources, most of which are used to be analyzed quantitatively according to existing methods . namely in the form of financial data, branch performance data and detailed data on opening and closing other branches. For branch opening, a vintage analysis is carried out on the area that is opening the branch. This analysis compares the area to the target val- ue vintage vintage given company and compare the value of non-performing Finance (NPF) to the value of non-performing loans (NPL) set by the Bank Indonesia’s Bank Rating Works that NPL 5%. The vintage that will be used is the current percentage (payment not in arrears) . The results showed that PQR Finance Enterprise closed or downgraded the status of several branch- es operating for less than two years on the grounds that the income or profit obtained was lower than the operational costs incurred which, if kept on running, would result in greater losses. Some branches are deemed not fulfill the requirements to be declared as branches based on the provisions of the Financial Services Authority. The basic error of opening a branch is also a reason. PQR Finance Enterprise sometimes only uses the reason of overcapacity in a branch to open another branch in a nearby location without a broader analysis of the feasibility of opening a branch